Interstitial lung disease associated with ALK inhibitors and risk factors: an updated comparative pharmacovigilance analysis - Dong, Junli; Li, Lulu; Deng, Tiying; Song, Haibin; Zhang, Shaohui; Zhong, Minyu (Frontiers in Pharmacology, 2024)
Background Inhibitors of the anaplastic lymphoma kinase (ALK) gene mutation are first-line treatments in patients with ALK-positive lung cancer. The FDA label warns of the risk of interstitial lung disease (ILD) in patients receiving ALK TKIs. However, ILD associated with ALK TKIs is not fully understood. The aim of this study was to characterize the features of ALK TKI-related ILD and to explore risk factors for ALK TKI-related ILD. Methods FDA’s Adverse Event Reporting System (FAERS) reports from 2011 Q1 to 2023 Q2 were extracted and combined. Standardized MedDRA queries (SMQs) were used to search for AEs at the preferred term (PT) level. Four algorithms were employed to quantify the signals of ILD associated with ALK TKIs. The risk of ILD was further analyzed using logistic regression. Results A total of 20,064 reports of ALK TKIs and 640 (3.2%) reports of ILD AEs were extracted. Significant disproportionality was detected in all five ALK TKIs. Interstitial lung disease and pneumonitis were the most common lung toxicities induced by ALK TKIs. Results of further analyses revealed a different spectrum of lung toxicity among the various TKIs. The median time to onset of ILD related to ALK TKIs was 53 days (Q1:12, Q3:209), and more than 70% of AEs occurred within the first 2 months. Logistic regression analysis and risk prediction model both showed that different ALK TKIs and their combination with PPIs, amlodipine, and magnesium oxide were independent risk factors for ILD (p<0.05). Conclusion ALK TKIs have different safety profiles regarding lung toxicity, which normally occurs within the first 2 months. Administration in combination with PPIs, amlodipine, and magnesium oxide significantly increases the risk of ILD. These results provide risk prediction for ILD related to ALK TKIs and support pharmacovigilance to promote safe prescribing in oncology.